2016
DOI: 10.15326/jcopdf.3.3.2015.0156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Barriers to Influenza Vaccination in Patients with Chronic Obstructive Pulmonary Disease: Analysis of the 2012 Behavioral Risk Factors Surveillance Survey

Abstract: Introduction Patients with chronic obstructive pulmonary disease (COPD) are at increased risk for influenza-related morbidity and mortality. Influenza vaccination is known to decrease influenza incidence, severity, hospitalizations, and mortality. Identification of barriers to influenza vaccination among patients with COPD may aid in efforts to increase vaccination rates. This study aims to identify predictors of influenza vaccination in COPD patients. Methods This study used data from the 2012 Behavioral Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
3
22
1
3
Order By: Relevance
“…Among the 60% of people with COPD in the low risk (high use) class for preventive vaccinations, almost all reported receiving the pneumonia vaccination (99.5%), yet only about half (55.3%) obtained their annual flu vaccination. Prior analyses of 2012 BRFSS data showed that close to 50% of patients with COPD were not vaccinated against influenza,11,66 which is similar to the flu vaccine rate reported here. The target HP 2020 recommendation for flu vaccination is 90% for adults living with chronic conditions 67.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Among the 60% of people with COPD in the low risk (high use) class for preventive vaccinations, almost all reported receiving the pneumonia vaccination (99.5%), yet only about half (55.3%) obtained their annual flu vaccination. Prior analyses of 2012 BRFSS data showed that close to 50% of patients with COPD were not vaccinated against influenza,11,66 which is similar to the flu vaccine rate reported here. The target HP 2020 recommendation for flu vaccination is 90% for adults living with chronic conditions 67.…”
Section: Discussionsupporting
confidence: 80%
“…Despite evidence that if a patient quits smoking, the patient can slow down the decline of lung functioning and can improve their chance of surviving COPD,8 nearly 40% of patients with COPD continue to smoke after a COPD diagnosis 9. Similarly, it is a national priority to promote flu vaccine uptake against respiratory viruses among patients with COPD;10 however, over half (51.5%) of patients with COPD in the United States report never receiving an influenza vaccination 11. Given their poor disease management practices, patients with COPD who smoke or have contracted the influenza virus experience negative health-related outcomes that compromise their quality of living 12,13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancak kronik akciğer hastalığı bulunan olgular göz önüne alındığında kadınların erkeklere göre daha yüksek oranda influenza aşısı olduğu görülmüştür. Benzer şekilde KOAH hastalarıyla yapılan bir araştırmada çok değişkenli regresyon analizinde erkek cinsiyetin aşılanma üzerine negatif etkili bir bağımsız değişken olduğu ve kadın olguların daha yüksek oranda aşılandıkları bulunmuştur(17).Yayınlanmış araştırmalarla uyumlu şekilde influenza aşısı ile aşılanma oranları pnömokok aşısı ile aşılanma oranlarından daha yüksek bulundu(18). Mevsimsel influenza aşısı pnömokok aşısından daha uzun süreden beri önerildiği için hem hekimlerin hem de hastaların influenza aşısı hakkında farkındalığı daha fazla olabilir.Araştırmamızın kısıtlılıklarından biri aşılanma oranlarının hastaların kendilerinin cevapladıkları anket sonucu belirlenmesi ve eczane bilgisiyle teyit edilmemesidir.…”
unclassified
“…This is not the first-time barriers to influenza immunization have been examined (9,10). However, studies in Iran based on our culture and economic situation is scarce (11).…”
mentioning
confidence: 99%